Preparation of Hard Tissues Like Bone or Cartilage for Shotgun Mass Spectrometry Analysis of the Proteome. Issue 10 (22nd October 2021) - Yuen, John W. M.; Li, K. K.; Lam, Thomas C.
Abstract: Proteomic analyses of intervertebral discs (IVDs) reveal information for understanding the fundamentals of biological processes and pathogenesis but also provide insights for novel pharmaceutical development. Sensitive mass spectrometry techniques and bioinformatics have advanced the detection and identification of proteins from any sample. Due to the challenges of catastrophic sample‐loss artifacts during hard‐tissue extraction, however, many researchers have omitted the cartilage endplates of IVDs for protein extraction, analyzing only the cellular components of the annulus fibrosus and/or nucleus pulposus. The full proteomic picture of IVDs is compromised without extracting proteins from intact IVDs. Here, we describe a novel preparation method using snap‐freeze grinding, which allows for mechanical disruption and customized chemical lysis of hard tissues such as bone or cartilage. This method replaces the time‐consuming and insufficient conventional tissue homogenization methods. Sample loss and contamination could be minimized during proteolysis by using an in‐solution protein digestion and desalting procedure. We demonstrate excellent proteome coverage with intact mouse IVDs by analyzing samples in a hybrid quadrupole time‐of‐flight tandem mass spectrometer. © 2021 Wiley Periodicals LLC.